The National Security and Intelligence Nexus in Nigeria: A Historical Analysis - Danladi Bot (Indonesian Journal of Education and Social Sciences, 2023)
Since the return to democracy in 1999, security has been a major issue in Nigeria in view of the continued ethno-religious conflicts, insurgency & terrorism, banditry, kidnappings, pipe-line vandalization and oil bunkering, sea piracy, and militancy that have continued to occur in the country. The detrimental effects of these national security challenges, has forced government and academics to direct their attention towards finding feasible solutions to Nigeria’s security conundrum. A close examination of existing academic works on National security challenges in the country reveals that very little attention has been paid to the understanding of the role of intelligence as a panacea or as a catalyst that has exacerbated insecurity in the country. In light of this, this paper examines the marriage between intelligence and national security. Focusing also, on the symbiotic relationship between the two and how they both work to reinforce or undermine each other. Methodologically, the paper adopted descriptive and analytic approach. Data for the paper was sourced through the secondary means of data collection. The study reveals that in Nigeria’s quest to establish sound intelligence and national security policies, it has not been able to fully take cognizance of its micro security, macro security and strategic security, and address adequately, the concerns therein. It also found out that, failure to gather intelligence comprehensively by the Nigerian intelligence services (using the full complements of their intelligence gathering paraphernalia) and also, failure to act in a timely fashion, to received intelligence, has sometimes been the reason why some violent altercations in the country have endured. Based on this, the paper recommends among others that for intelligence to be successful in reducing insecurity in Nigeria, the intelligence related services in the country, need to synergize their efforts in the promotion of Nigeria’s national security strategy. Hopefully, this research study could assist various stakeholders in policy making when it comes to the application of intelligence in dealing with national security threats.